Career-Related Characteristics Towards Career Certainty of Vocational College Students - Mohd Puad, Mohd Hazwan; Mohamad, Aslina; Mat Rashid, Abdullah (Journal of Technical Education and Training, 2023)
Career path certainty in this era of innovation, digitalization, and globalization is increasing and continues to be the decisive factor in career selection by many people in the fast-growing, unpredictable, and highly competitive job market. This situation has forced students to make career choices as the first step to ensure that the available human resources are in line with the demand in the labor market. This study aims to determine the role of career-related characteristics in the relationship to career certainty among Vocational College students in Selangor. The career-related characteristics included in this study are career planning, career exploration, self-efficacy, outcome expectations, and career goals. This research is a quantitative and correlational study conducted on first-year Vocational College students in Selangor. Using simple random sampling, 230 students were selected as research respondents. The results showed that career planning, career exploration, self-efficacy, outcome expectations, and career goals showed an insignificant but moderate positive relationship with career certainty. This study provides a basis for planning career-related learning and development programs at the pre-university level. The study recommends that teachers actively initiate student career exploration activities during learning.